RESEPSI KHALAYAK PEMBACA BERITA TRAGEDI ANAK (AQJ) PADA MEDIA ONLINE - Rika Novitasari; Hedi Pudjo Santosa; Much Yulianto; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2015)
This research based on the rampant of news about children tragedy in mass media. Childrenare exploited and reported in news excessively, and the news ignore children’s right to beprotected from publicity. Online media is one of the public choice that reprimanded by presscouncil in reporting AQJ accident, because a lot of media showed the face and wrote hisidentity clearly and didn’t place him as vict im of the systemThis research aims to understand audiences’ reception of the purpose of online mediain AQJ accident news. The type of this research is qualitative research used receptionanalysis to discover the reception of the audiences with different experience and background.This research show three types of audience position on AQJ news. The majority of audiences are in negotiated and interpret AQJ accident news as important news because it harms to others, detailed information often expected but they thought that underage children need to be protected from publicity, related to their identity and another aspect that could bother their psychological. Audience who are in dominant reading, interpret the news as natural news that gives positive benefit and important to note audiences widely, and have to be reported in detail. While another audience who are in oppositional reading interpret that news about children tragedy didn’t need to be published, according to the audience news about children tragedy will violate children’s psychology who are still developing and the news about AQJ accident on online media as unobjective and excessive news.Keywords: News, Tragedy, Children, Reception